Bacteriuria in Pregnant and Non Pregnant Women in Benghazi - Comparative Study - Al-Mehdawi, Khaled Ali Mohamed (Arab Journal for Sciences and Research Publishing, 2015)
Background: Bacteriuria is associated with significant maternal and foetal risks. However, its prevalence is not well known in our community. Objectives: Determine the prevalence and predictors of bacteriuria in women of the Benghazi, Libya as well as the antibiotic sensitivity patterns of bacterial isolates. Methods: Across-sectional study was carried out amongest pregnant and non-pregnant women attending many polyclinics in Benghazi. We recruited 120 consenting women (60 pregnant and 60 non pregnant) for the study. Demographic and clinical data were collected using structured questionnaire. Clean catch midstream urine was collected from each participant. Samples were examined biochemically, microscopically and by culture. Significant bacteriuria was defined as the presence of 105 bacteria per ml of cultured urine. Identification and susceptibility of isolates was performed using API (BioMerieux, France Company) . Results: Significant bacteriuria was found in the urine of 13.3 % (16) of all women with prevalence of 16.7% in pregnant women. Asymptomatic bacteriuria was detected in 8.3 % (10). The most frequent isolates were Staphylococcus aureus (31.2%), E. coli (25%), Staphylococcus saprophyticus (18.9%), and were sensitive to gentamycin (GN) 87.5%, azithromycin (AZM)75%, and the less effective antibiotics were cephalexine (CL) and ampicillin (AMP). Conclusion: Bacteriuria is frequent in women particularly pregnant women suggesting the need for routine screening by urine culture, which would allow early treatment to avoid the complications. In addition, UTI infections appears to be multifactorial.